FACILITATING INTERCULTURAL COMMUNICATIVE COMPETENCE OF ADULT LEARNERS IN THE CONTEXT OF HIGHER EDUCATION INTERNATIONALISATION - Jan-Urban Sandal; Tetiana Kolenichenko; Anna Verbytska; Hanna Dyvnych (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
The article is aimed at the assessment of the educational needs of the active older adults, studying their motives to learn English. The hypothesis of the research is that effective formation of the intercultural communicative competence in active older adults is carried out on the basis of the specially developed educational programme "Foreign language (English)" and the communicative-oriented approach in teaching within the framework of lifelong learning. In order to achieve the purpose of the research, a set of scientific methods was used: analysis, synthesis, comparing, generalisation, questioning, testing and interviewing. Respondents were 64 active older adults who were the students of the Centre of education and social activity for elderly people "Second Youth". The majority of respondents (51%) showed the increasing level of intercultural communicative competence after the completion of the English language course for ten months. The application of the suggested in the article model will improve the level of English competence, the motivation for learning English, the ability to communicate and interact in the intercultural environment, formation of positive and tolerant perception of intercultural features, the general level of self-confidence, as well as satisfaction of the need for extending communication with other people.